(untitled) (Research, Society and Development, 2021)
The present work aims to study the effect of hydroalcoholic extracts of three carqueja species (Baccharis trimera, Baccharis dracunculifolia and Baccharis gaudichaudiana) at different concentrations on the germination and initial growth of lettuce (Lactuca sativa) and the identification of volatile compounds present in these species . Lettuce seeds were distributed in a gerbox containing germitest paper. The experimental design used was completely randomized (DIC) in a bifactorial scheme (3x5), representing three species of carquejas and five concentrations of extracts: 0.00, 0.02, 0.03, 0.04 and 0.05%, with four repetitions. The experiment was maintained for a period of seven days in B.O.D. with a temperature of 17.5 °C. The chemical analysis of the constituents belonging to the three species analyzed was performed by gas chromatography coupled with mass spectrometry (CG/MS - Shimadzu, model QP 5050A). The chemical composition of the carquejas resulted in 29 different chemical compounds, each Baccharis species has a specific compound that represents between 24 and 25% of its total chemical composition, namely (-)-Spathulenol (24%), Alloaromadendrene oxide (25%) and 3-Cyclohexen-1-one, 3,5,5-trimethyl- (24.63%) for B. dracunculifolia, B. gaudichaudiana and B. trimera, respectively. The results indicate that B. trimera has allelopathic potential to favor lettuce germination. The species B. dracunculifolia and B. gaudichaudiana did not influence the germination of lettuce seeds in the analyzed concentrations. The extracts of B. trimera, B. dracunculifolia and B. gaudichaudiana negatively influenced the root length and germination speed index (IVG) with the increase in extract concentrations.